Pengaruh motivasi belajar terhadap prestasi peserta didik di sekolah - Rafli, Muhammad (Maliki Interdisciplinary Journal, 2024)
The purpose of this report is to find out how learning inspiration influences student achievement at school. This exploration centers on the role of educators in providing motivation for students to learn. These ideas are very important for improving student achievement. As is known, students do not have the motivation to learn. This will have an impact on his progress in learning. Therefore, teachers must try to increase students' interest in learning and encourage them to be more motivated to excel at school. Education should be able to influence students to excel and adapt as best as possible to their environment, so that they can participate well in society. However, experts found that students' desire to learn was influenced by very low levels of motivation. This diary research uses a methodology (book research) which involves writing as the article. The results of this study show that learning inspiration influences students' learning practice, especially their learning achievement. Student learning achievement is positively correlated with their level of inspiration. On the other hand, it gets lower.